Current treatment of congenital pseudarthrosis of the tibia: a systematic review and meta-analysis. Issue 6 (November 2018) - Kesireddy, Nithin; Kheireldin, Rowida K.; Lu, Alex; Cooper, Jonathan; Liu, Jiayong; Ebraheim, Nabil A.
Abstract : To compare the current treatments for congenital pseudarthrosis of tibia, a total of 33 studies were reviewed. Vascularized fibular graft with external fixation or combined fixation had the fastest time till initial union ( P <0.05). Bone morphogenetic protein had no advantage in terms of initial union, time till union, and refracture rates. This meta-analysis supports that fixation methods with corticocancellous bone autograft utilizing the combined technique of Ilizarov external fixation and intramedullary rod stabilization ensure a statistically significant reduction in the number of refractures compared with standalone fixation methods and would be the preferred method for preventing long-term complications in patients with congenital pseudarthrosis of tibia. Abstract : Supplemental Digital Content is available in the text.